Proteomics Analysis of the Spinal Dorsal Horn in Diabetic Painful Neuropathy Rats With Electroacupuncture Treatment - Yu, Xiangmei; Chen, Xiaomei; Liu, Weiting; Jiang, Menghong; Wang, Zhifu; Tao, Jing (Frontiers in Endocrinology, 2021)
Background Clinical evidence demonstrates that electro-acupuncture (EA) of the Zu sanli (ST36) and Shen shu (BL23) acupoints is effective in relieving diabetic painful neuropathy (DPN); however, the underlying molecular mechanism requires further investigation, including the protein molecules associated with EA’s effects on DPN. Methods Sprague-Dawley adult male rats (n =36) were randomly assigned into control, DPN, and EA groups (n=12 each). After four weeks of EA treatment, response to mechanical pain and fasting blood glucose were analyzed. A tandem mass tag (TMT) labeling approach coupled with liquid chromatography with tandem mass spectrometry was used to identify potential biomarkers in the spinal dorsal horn. Further, proteomics analysis was used to quantify differentially expressed proteins (DEPs), and gene ontology, KEGG pathways, cluster, and string protein network interaction analyses conducted to explore the main protein targets of EA. Results Compared with the DPN model group, the mechanical pain threshold was significantly increased, while the fasting blood glucose levels were clearly decreased in EA group rats. Proteomics analysis was used to quantify 5393 proteins, and DEPs were chosen for further analyses, based on a threshold of 1.2-fold difference in expression level (P < 0.05) compared with control groups. Relative to the control group, 169 down-regulated and 474 up-regulated proteins were identified in the DPN group, while 107 and 328 proteins were up- and down-regulated in the EA treatment group compared with the DPN group. Bioinformatics analysis suggested that levels of proteins involved in oxidative stress injury regulation were dramatically altered during the EA effects on DPN. Conclusions Our results provide the valuable protein biomarkers, which facilitates unique mechanistic insights into the DPN pathogenesis and EA analgesic, antioxidant stress and hypoglycemic effect.